Ze studiów nad początkami kultury łużyckiej w zachodniej Wielkopolsce - Kaczmarek, Maciej (Folia Praehistorica Posnaniensia, 2018)
The article is an attempt to explain the origin of the Lusatian culture in western Wielkopolska on the basis of available archaeological evidence. The author inscribes the major role in the formation of the early Lusatian groups in western Wielkopolska to communities from Lower Silesia. From this territory culture impulses radiated along the Odra river, which led to the emergence of the early assemblages of the Urnfield culture in western Wielkopolska and the Lubusz Lands at the beginning of phase III of the Bronze Age.